Conference Report: REDD+ related forest monitoring remains a key issue: a report following the recent UN climate conference in Doha. Issue 2 (April 2013) - Sanz-Sanchez, Maria; Herold, Martin; Penman, Jim
The issue of forest monitoring for REDD+ was a focus area at the recent UN climate conference in Doha, Qatar. Although the expected Decision of the COP on national-level forest monitoring systems and measurement, reporting and verification for REDD+ activities was not finalized, the elements in the draft decision that is available and the in-depth discussions evident from side events and processes show the level of technical work that is underway, indicate good convergence, and suggest that resolving the methodological issues need not be a barrier to political agreement.